The first success in utilizing the RUBY reporter gene for rice transformation in Vietnam - Pham, Thi Mai Anh; Ly, Khanh Linh; Chu, Khanh Linh; Phan, Quyen; Bui, Phuong Thao; Le, Hong Diep; Nguyen, Xuan Cuong; Chu, Hoang Ha; Do, Tien Phat (Vietnam Journal of Biotechnology, 2026)
To date, several reporter genes have been developed, such as GFP, GUS, and luciferase. However, GFP and luciferase genes are costly and require modern equipment, while GUS requires sample destruction. To overcome these limitations, the RUBY gene is considered a promising alternative. RUBY is an artificial open-reading frame, encoding CYP76AD1, L-DOPA 4,5-dioxygenase, and glucosyltransferase, which are key enzymes involved in the biosynthesis of betalain, which displays a red-colored pigment, providing a visual marker for transformation events. In this study, the RUBY gene was successfully transformed into the model rice variety Kitaake via the Agrobacterium-mediated method. The activity of the RUBY gene was visually detected by red spots in calli and somatic embryos through the rice transformation and regeneration procedure. Moreover, the presence and expression of this reporter gene were confirmed by PCR and the red coloration in the regenerated rice lines. The RUBY gene was stably expressed in transgenic rice lines under both in vitro and greenhouse conditions and was heritable in the T1 generation, without exhibiting any adverse effects on plant growth and development. This result demonstrates the potential of RUBY as a visual selection marker for rice transformation in Vietnam and opens the door to further applications in other important crops.